The Construction of Soviet Ethnography and “The Peoples of Siberia”. - Anderson, David G.; Arzyutov, Dmitry V. (History & Anthropology, 2016)
The multi-generation book project "The Peoples of Siberia" enabled a group of Leningrad-based scholars to reshape their museum into a Soviet ethnographic community. This article analyses the face-to-face performances, the legalistic stenographic documentation, the collective crafting of a single authoritative style, and a unique temporal frame as an important background to understand a hallmark volume in Siberian studies. The authors argue that the published volume indexes nearly thirty years of scholarly debates as much as it indexes the peoples it represents. The article concludes with a critical discussion of how this volume was translated and received by a Euro-American readership influencing the perception of Siberian peoples internationally. It also links the volume to contemporary post-Soviet publication projects which seem to retrace the same path. The article is based on extensive archival work and references collections recently discovered and which are presented for publication here for the first time.